A mediação do professor e a aprendizagem de geometria plana por aluno com transtorno do espectro autista (síndrome de Asperger) em um laboratório de matemática escolar - Delabona, Stênio Camargo (2016)
Thinking of education as a process of human formation, based on social, cultural, historical relations in an inclusive context, is a challenge for teachers and researchers in all fields of knowledge. In this sense, this research aims to contribute to the inclusive education in mathematics of students with autistic spectrum disorders. This study set out to analyze the meaning given to the geometric object of study by a student with Asperger syndrome, through the application of a pedagogical proposal, which would favor designing activities in the School Mathematics Laboratory (SML). The object of the research is mediations designed in the SML and their impact on the process of argumentation and geometric learning by a student with Asperger syndrome. The research problem consists of three questions: (1) What are the mediations designed by a teacher of Mathematics for students with Asperger syndrome involved in plane geometry activities in an SML? (2) What mediator actions emerge in collective geometrical learning activities when a student with Asperger syndrome is involved? (3) What arguments are used by a student with Asperger syndrome in solving plane geometry problems? This study takes a qualitative approach and the method used was that of a case study of observation. The procedures and methodological resources adopted in the research involved learning workshop records drawn up with the subject of the research, interviews, dialogues, record and documentary analyses. The underlying theoretical assumptions were based on the Cultural-Historical Theory. The results show evolution in the process of argumentation and in solving mathematical activities on the part of the student. This denotes better manipulation of mathematical signs and also the acquisition of scientific concepts. Mediations and social interactions between students and the teacher were crucial to the development and learning of geometrical concepts with greater meaning for the student with Asperger syndrome. As an educational product of this research, a CD was designed containing the script of all the workshops held in the SML, the planning, reasons and needs which led to its application.